2018
DOI: 10.1038/s41598-018-28080-y
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical properties of cationic dyes captured in the mesoscale channels of micron-sized metal-organic framework crystals

Abstract: The optical properties of dye molecules in confined spaces can differ from the solution phase due to confinement effects. Pre-organized mesoscale channels of metal-organic frameworks (MOFs) are very suited for hosting various dyes, and the robust frameworks often render the encapsulated dyes with certain preferential geometries, which are different from those found in solution. Furthermore, pre-organized open channels can efficiently guide the uniform and unique spatial distribution of dye molecules in a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Although solid literature exists on the confinement effect for zeolites, knowledge of such phenomenon in materials with larger pores is still being built . The Kim group, for example, has shown that dyes confined in the mesopores of MOFs have photophysical properties that differ significantly from the nonconfined molecules . Another interesting work was published by the Goswami group, in which the authors were able to conduct polyol metal nanoparticles synthesis inside the pores of polystyrene and silica gel particles .…”
Section: Resultsmentioning
confidence: 99%
“…Although solid literature exists on the confinement effect for zeolites, knowledge of such phenomenon in materials with larger pores is still being built . The Kim group, for example, has shown that dyes confined in the mesopores of MOFs have photophysical properties that differ significantly from the nonconfined molecules . Another interesting work was published by the Goswami group, in which the authors were able to conduct polyol metal nanoparticles synthesis inside the pores of polystyrene and silica gel particles .…”
Section: Resultsmentioning
confidence: 99%
“…We also observed similar phenomenon when we used EtOH for encapsulation of various cationic dyes. 6 Nonetheless, we believe that the metal–ligand connectivity may not be seriously damaged because trans -[Co(en) 2 Cl 2 ] + ions did not leach out during catalytic reactions.…”
Section: Resultsmentioning
confidence: 94%
“… 5 Several cationic dyes were also effectively incorporated into InBTB to give a series of dye@InBTB MOFs with good optical properties. 6 These examples clearly suggest that the cation-exchange-driven generation of functional MOFs is a promising strategy to develop new MOF systems with diverse functions.…”
Section: Introductionmentioning
confidence: 99%
“…Confining dye molecules in spaces not much larger than the molecules themselves 1 can drastically affect their optical properties. Both absorption and emission of dyes can be altered by encapsulation within the cavities of molecular cages, 2 metal–organic frameworks, 3,4 and protein molecules. 5 For example, cucurbit[8]uril (CB[8]) was shown to stabilize the monomeric form of perylene dyes, thus preventing undesired aggregation and enabling strong fluorescence in aqueous media.…”
mentioning
confidence: 99%